Analisis Lembar Kerja Peserta Didik (LKPD) Praktikum Fisika di SMA Negeri Kabupaten Toraja Utara - Silka, Silka; Bethony, Ftans R. (Universitas PGRI Semarang, 2022)
This study aims to (1) describe the feasibility of the contents of the physics practicum student worksheet (LKPD) (2) describe the feasibility of presenting the physics practicum LKPD student worksheet (3) describe the language feasibility of the physics practicum student worksheet (LKPD) and (4) to describe the overall feasibility of the physics practicum student worksheet (LKPD). This research is a quantitative descriptive study. The subjects in this study were teachers and the head of the physics laboratory which was carried out in eight SMA Negeri North Toraja Regency. Data collection techniques were carried out through student worksheet questionnaires (LKPD), observations and interviews as supporting data. the percentage of 51.79%. While the LKPD analysis of the feasibility of presentation obtained a percentage of 52.68% and for the LKPD language analysis a percentage of 66.43% was obtained quite decent.Keywords: Analysis, Student Worksheet, State High School.